1999
DOI: 10.1016/s0378-1097(99)00250-5
|View full text |Cite
|
Sign up to set email alerts
|

Low virulence of a morphological Candida albicans mutant

Abstract: The virulence of Candida albicans 92P, a morphological mutant unable to filament, was assayed in an experimental model of systemic candidiasis in three strains of mice with different susceptibilities to the infection. The mortality parameters studied pointed to the low virulence of this mutant strain. Study of the fungal load of C. albicans 92P in kidneys and brain revealed the presence of low numbers of CFUs and a high percentage of clearance, particularly in the brain. Adhesion studies demonstrated a reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 19 publications
2
17
0
Order By: Relevance
“…The extremely low virulence and the lack of tissue damage of this agerminative C. albicans mutant strain (92¢) in the murine systemic infection have been described Med Microbiol Immunol (2001) 189: 153±160 previously [13]. These features make this strain an excellent tool for the study of the defence mechanisms against its infection.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…The extremely low virulence and the lack of tissue damage of this agerminative C. albicans mutant strain (92¢) in the murine systemic infection have been described Med Microbiol Immunol (2001) 189: 153±160 previously [13]. These features make this strain an excellent tool for the study of the defence mechanisms against its infection.…”
Section: Introductionmentioning
confidence: 91%
“…Host resistance to infection by C. albicans involves a number of speci®c and non-speci®c factors that have been most extensively explored in the mouse infection model [12,13,19,32]. This model closely reproduces, both in its nature and severity, the lesions seen in the human disease [38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported that strains of C. albicans that cannot form hyphae are avirulent in mice (16,34,41,69). Thus, the characterization of the genes involved in dimorphism may lead to the discovery of new treatments for pathogenic fungi.…”
mentioning
confidence: 99%
“…It is thought that this ability is related to pathogenicity, which is reduced by the inhibition of hyphal growth, because morphological mutants defective in hyphal growth exhibit low virulence compared to the parental strain [2]. Understanding the dimorphism and screening for hyphal growth inhibitors should lead to the development of new antifungal therapies.…”
Section: Introductionmentioning
confidence: 99%